2020
DOI: 10.1055/s-0040-1709983
|View full text |Cite
|
Sign up to set email alerts
|

Risk Factors for Postpartum Maternal Infection Following Spontaneous Vaginal Delivery Complicated by Chorioamnionitis

Abstract: Objective Guidelines for the management of chorioamnionitis include intrapartum antibiotics, while postpartum antibiotics after spontaneous vaginal delivery (SVD) are reserved high-risk women. Our objective is to describe the incidence of and risk factors for postpartum infection after SVD complicated by chorioamnionitis. Study Design This is a retrospective study of SVDs with clinically diagnosed chorioamnionitis at a single center. The primary outcome was a composite of postpartum infection. Women … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
3
0
4

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 17 publications
0
3
0
4
Order By: Relevance
“…Spontaneous vaginal delivery (SVD) is a vaginal delivery that happens without using tools to help pull the baby out. This was associated with neonatal septicaemia in our study, here babies could have been exposed to maternal vaginal and fecal bacteria through per-vaginal examination during labour and delivery or as a result of bacteria being introduced into the cervical canal causing vertical transmission from infected mothers to the babies or chorioamnionitis caused by bacteremia that occurs when the amniotic sac breakes before birth [ 55 , 56 ]. which was contrary to other studies that showed cesarean section was more associated with culture-positive cases [ 57 ].…”
Section: Discussionmentioning
confidence: 99%
“…Spontaneous vaginal delivery (SVD) is a vaginal delivery that happens without using tools to help pull the baby out. This was associated with neonatal septicaemia in our study, here babies could have been exposed to maternal vaginal and fecal bacteria through per-vaginal examination during labour and delivery or as a result of bacteria being introduced into the cervical canal causing vertical transmission from infected mothers to the babies or chorioamnionitis caused by bacteremia that occurs when the amniotic sac breakes before birth [ 55 , 56 ]. which was contrary to other studies that showed cesarean section was more associated with culture-positive cases [ 57 ].…”
Section: Discussionmentioning
confidence: 99%
“…Se informa leucocitosis en aproximadamente el 70-90% de los casos de corioamnionitis clínica. Sin embargo, la leucocitosis aislada en ausencia de otros signos o síntomas tiene un valor limitado, ya que puede ser inducida por varias otras afecciones, incluido el trabajo de parto y el uso de esteroides (13). Por lo tanto, el monitoreo rutinario del conteo de glóbulos blancos en mujeres de alto riesgo (ruptura prematura de la membrana pretérmino) en ausencia de signos clínicos de corioamnionitis no es útil.…”
Section: Discussionunclassified
“…Otros parámetros de laboratorio que incluyen altos niveles de proteína C reactiva (PCR), proteína de unión a lipopolisacárido, molécula de adhesión intercelular soluble-1 e interleucina-6 se han asociado con un mayor riesgo de corioamnionitis en el contexto de RMP o parto pretérmino (13). Sin embargo, su utilidad para el diagnóstico o la predicción de corioamnionitis como parte de la práctica clínica habitual no está establecida.…”
Section: Discussionunclassified
See 1 more Smart Citation
“…There are multiple risk factors for postpartum endometritis including delivery mode ( 62 ), early and moderately preterm birth ( 63 , 64 ), BMI ( 65 ), bacterial colonization with group A or group B Streptococcus ( 66 ), chorioamnionitis, prolonged rupture of membranes, prolonged operative time, poor nutrition, bacterial vaginosis, and multiple vaginal examination ( 67 , 68 ). Of these risk factors associated with PPE, there are now substantial evidence linking the association of birth mode (CS or vaginal delivery) with PPE ( 40 , 41 ).…”
Section: Methodsmentioning
confidence: 99%